2014
DOI: 10.1073/pnas.1400568111
|View full text |Cite
|
Sign up to set email alerts
|

Acentriolar mitosis activates a p53-dependent apoptosis pathway in the mouse embryo

Abstract: Significance Centrioles form the core of centrosomes, which organize cilia and interphase and spindle microtubules in animal cells, but centrosome function has not been defined in mammals in vivo. We show that mouse embryos that lack centrioles and centrosomes survive to midgestation, when they lack primary cilia and cilia-dependent signaling. Despite the absence of centrosomes, bipolar spindle formation, chromosome segregation, cell-cycle profile, and DNA damage response are normal in the mutants. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
208
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(238 citation statements)
references
References 79 publications
25
208
4
1
Order By: Relevance
“…These data agree with studies demonstrating that CPAP is critical for controlling the cleavage plane of mitotic neural progenitors (Insolera et al , 2014; Bazzi & Anderson, 2014; Garcez et al , 2015; Appendix Fig S10). Finally, when analyzing apical progenitor cilia extending into the lateral ventricle, Seckel organoids showed increased numbers and longer cilia compared to WT organoids, suggesting retarded cilium disassembly consistent with our results from fibroblasts and NPCs experiments (Fig 6C).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These data agree with studies demonstrating that CPAP is critical for controlling the cleavage plane of mitotic neural progenitors (Insolera et al , 2014; Bazzi & Anderson, 2014; Garcez et al , 2015; Appendix Fig S10). Finally, when analyzing apical progenitor cilia extending into the lateral ventricle, Seckel organoids showed increased numbers and longer cilia compared to WT organoids, suggesting retarded cilium disassembly consistent with our results from fibroblasts and NPCs experiments (Fig 6C).…”
Section: Resultssupporting
confidence: 91%
“…These findings are consistent with our NPCs experiments as well as with the observation of Tctex‐1‐mediated defective cilium disassembly triggering premature neuronal differentiation (Li et al , 2011; Fig 6B). Importantly, apoptotic cell deaths in Seckel and WT organoids did not differ which excludes the involvement of apoptotic cell death‐mediated NPCs loss (Marthiens et al , 2013; Bazzi & Anderson, 2014; Appendix Fig S12). …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…89 Interestingly, disruptions in centrosome biogenesis have been shown to lead to cell cycle exit defects, genome instability and increases in apoptosis reminiscent of the Ehmt2 loss-of-function phenotype in vivo. 94,95 Whether Ehmt2 is required to regulate the expression or activity of individual genes in the centrosome biogenesis pathway has not been studied, and thus the mechanism of centrosome disruption is not clearly defined. Nonetheless, it seems likely that the genome instability resulting from Ehmt2 loss could result from both spindle attachment defects and centrosome defects.…”
Section: Emerging Roles Of Ehmt2mentioning
confidence: 99%
“…The wild-type p53 protein is able to exert a range of anti-proliferative effects, including the induction of apoptosis and causing a marked increase in the sensitivity of these cells to DDP (18,19). However malignancies with mutated p53 genes and aberrant p53 proteins in laboratory studies and one clinical study have been observed to be less responsive to chemotherapy agents that induce DNA damage, such as DDP (20,21).…”
Section: Discussionmentioning
confidence: 99%